2022
DOI: 10.1021/acsapm.2c00001
|View full text |Cite
|
Sign up to set email alerts
|

Nanocellulose/Nisin Hydrogel Microparticles as Sustained Antimicrobial Coatings for Paper Packaging

Abstract: Hydrogels composed of biomaterials are promising drug delivery systems. In this study, we prepared an antibacterial hydrogel by incorporating the antimicrobial peptide nisin into bagasse cellulose nanofibrils, followed by mechanic shearing to obtain hydrogel microparticles as antimicrobial coatings for paper packaging. The concept of combining nisin with a hydrogel network helps to reduce the nisin depletion disadvantage in a nisin alone coating while achieving a prolonged antibacterial efficacy in application… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…(a) Development of a food packaging antibacterial hydrogel based on gelatin, chitosan, and 3‐phenyllactic acid for the shelf‐life extension of chilled chicken (Y. N. Liu et al., 2022). (b) Schematic illustration of forming the TOCNF/nisin hydrogel (P. Lu et al., 2022). (c) Scheme illustration of hydrogel microparticles preparation and application as coatings on paper (P. Lu et al., 2022).…”
Section: Applications Of Peptide Hydrogels In Food Sciencementioning
confidence: 99%
See 1 more Smart Citation
“…(a) Development of a food packaging antibacterial hydrogel based on gelatin, chitosan, and 3‐phenyllactic acid for the shelf‐life extension of chilled chicken (Y. N. Liu et al., 2022). (b) Schematic illustration of forming the TOCNF/nisin hydrogel (P. Lu et al., 2022). (c) Scheme illustration of hydrogel microparticles preparation and application as coatings on paper (P. Lu et al., 2022).…”
Section: Applications Of Peptide Hydrogels In Food Sciencementioning
confidence: 99%
“…(b) Schematic illustration of forming the TOCNF/nisin hydrogel (P. Lu et al., 2022). (c) Scheme illustration of hydrogel microparticles preparation and application as coatings on paper (P. Lu et al., 2022). (d) Zone of inhibition test of paper with different coating weight against L. monocytogenes (P. Lu et al., 2022).…”
Section: Applications Of Peptide Hydrogels In Food Sciencementioning
confidence: 99%
“…Antimicrobial tests in vitro revealed that the film effectively inhibited the growth of E. coli, L. innocua, and A. f umigatus within 24 h. The release amount and antimicrobial activity of the film increased with increasing enzyme concentration, RH, and exposure time. In addition, Lu et al 37 blended nisin with TEMPO-oxidized bagasse cellulose nanofiber colloidal suspensions to form an antimicrobial hydrogel with a rich network structure through electrostatic interaction. The hydrogel was then processed into particles using a mechanical shear treatment and coated on packaging paper as a slow-release antimicrobial coating (Figure S8a).…”
Section: Safp Materials Thatmentioning
confidence: 99%
“…Ideally, the activation and release of antimicrobial ingredients should occur when the packaging is in contact with food rather than being released in large quantities during the fabrication, assembly, or transportation of the packaging itself. Various triggering mechanisms have been employed, such as changes in temperature, humidity/moisture, light, pH, and enzyme, which induce relaxations or other subtle changes in the packaging matrix without compromising its integrity and mechanical properties. These changes stimulate the movement and migration of antimicrobial active ingredients toward external media (i.e., air or food).…”
Section: Working Mechanism Of a Safp Antimicrobial Systemmentioning
confidence: 99%
“…), man-made biodegradable polymers (Poly-(butylene adipate-co-terephthalate), poly (lactic acid), Polypropylene carbonate, Polyhydroxyalkanoates, Polybutylene succinate, etc.) are the focus of researchers in recent years, which will be conducive to the overall development of the economy and society, and the harmonious coexistence of human and nature [ 3 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%